(untitled) (TERRA LATINOAMERICANA, 2023)
Due to high pressure for the urbanization of areas of the saline-sodic soils (SSS) around the former Texcoco lake, Sate of Mexico, it is important to find strategies for tree planting. The aim of the study was to determine the response of five tree species; Pinus greggii, P. pseudostrobus, P. ayacahuite, P. leiophylla and as reference species Psidium guajava, established in holes filled with an alternative substrate (HAS) in SSS. Fif ty holes 1 m depth and 0.60 m in diameter were excavated and filled with an alternative substrate. The pH, electrical conductivity (EC), mechanical resistance (MR), volumetric water content, relative water content (RWC) in plant tissue and survival at 280 days were measured. The HAS presented lower values with respect to the control (SSS): in pH, 8.99 vs. 9.95; in EC, 2.58 vs. 8.19 dS m-1; in volumetric water content, 0.41 vs. 1.06 cm3 cm-3; and in mechanical resistance, 1.72 vs. 2.53 MPa. The RWC increased at 120 days in P. ayacahuite (from 74.7 to 81.5%) and P. leiophylla (75.2 to 77.5%), while in P. guajava it decreased (92.8 to 75.5%). Survival af ter 280 days for P. guajava (70%) exceeded that of pines (1.67%). P. guajava was the species the better performed, whereas pines did not survived salinity. HAS was helpful in the establishment of tree species by providing healthier environment despite the adverse conditions of the SSS.